2019
DOI: 10.1177/2045894019878598
|View full text |Cite
|
Sign up to set email alerts
|

Diminished right ventricular function at diagnosis of pulmonary hypertension is associated with mortality in bronchopulmonary dysplasia

Abstract: Pulmonary vascular disease and resultant pulmonary hypertension (PH) have been increasingly recognized in the preterm population, particularly among patients with bronchopulmonary dysplasia (BPD). Limited data exist on the impact of PH severity and right ventricular (RV) dysfunction at PH diagnosis on outcome. The purpose of this study was to evaluate if echocardiography measures of cardiac dysfunction and PH severity in BPD-PH were associated with mortality. The study is a retrospective analysis of the echoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 57 publications
1
20
0
1
Order By: Relevance
“…About 25% of infants with moderate to severe BPD develop PH 3,4 that affects heart and lungs, greatly increasing mortality (47% of BPD infants die 2 years after diagnosis of PH). [5][6][7] Compared to BPD without PH, BPD-PH is associated with suboptimal somatic growth and neurodevelopmental outcome, 8,9 and higher rates of tracheostomy, increased use of supplemental oxygen, feeding problems, and frequent hospital admissions. 10 Young adults born preterm (very low birth weight ≤1500 g; average gestational age 28 weeks) are at increased risk for PVD, PH, and right ventricular (RV) dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…About 25% of infants with moderate to severe BPD develop PH 3,4 that affects heart and lungs, greatly increasing mortality (47% of BPD infants die 2 years after diagnosis of PH). [5][6][7] Compared to BPD without PH, BPD-PH is associated with suboptimal somatic growth and neurodevelopmental outcome, 8,9 and higher rates of tracheostomy, increased use of supplemental oxygen, feeding problems, and frequent hospital admissions. 10 Young adults born preterm (very low birth weight ≤1500 g; average gestational age 28 weeks) are at increased risk for PVD, PH, and right ventricular (RV) dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Premature newborns, and particularly those with BPD, are at-risk for PH and RV dysfunction. 12,13,17,[43][44][45] Specifically, degree of RV dysfunction at diagnosis of PH seems to be associated with poorer outcomes in this vulnerable population. 17 The RV primarily contracts in a longitudinal fashion, with the tricuspid valve plunging toward the RV outflow tract; measure of RV function, therefore, includes the TAPSE which measures the longitudinal distance of movement of the tricuspid valve during systole.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,17,[43][44][45] Specifically, degree of RV dysfunction at diagnosis of PH seems to be associated with poorer outcomes in this vulnerable population. 17 The RV primarily contracts in a longitudinal fashion, with the tricuspid valve plunging toward the RV outflow tract; measure of RV function, therefore, includes the TAPSE which measures the longitudinal distance of movement of the tricuspid valve during systole. [46][47][48][49] STE uses the pixels composing the ECHO image to track cardiac movement during the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a small pediatric PH study, strain was found to be an earlier predictor of RV dysfunction [ 50 ]. A recent study in neonates with BPD-PH has suggested that an RV peak longitudinal strain greater than −14 is a discriminative marker of BPD-PH [ 51 ]. The limitations of strain and strain rate measurements are the relatively low temporal solution of 2D speckle tracking in the presence of high heart rates and the long post-processing times [ 25 ].…”
Section: Global and Regional Functional Assessment Of The Rvmentioning
confidence: 99%